Peran Ayah dalam Pendidikan Anak Usia Dini di Era Digital - Suryadi; Ayuningrum, Desy; Nopiana (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
Early childhood is an individual who was starting from 0-6 years was having the process of the rapid development. The children were identical to play. In the child’s daily activities often do thr game. The game is something that must be considered as a means to the development of the physical motor for early childhood. Along with technological progress, in the digital age at this time the child is usually done a game in gadget. This study aims to obtain a pictures of the development of the physcal motor early childhood in the digital age. The subject of this study consist of 3 children aged 5-6 years consisting of 1 boys and 2 girls. The result of derived from this research is the show the development of the physical and motor her.